Detecção de intrusos descentralizada em redes de sensores sem fio - Ana Paula Ribeiro da Silva (2005)
Wireless sensor networks (WSNs) have many potential applications. Furthermore, in many scenarios WSNs are of interest to adversaries and they become susceptible to some types of attacks since they are deployed in open and unprotected environments and are constitutedof cheap small devices. Preventive mechanisms can be applied to protect WSNs against some types of attacks. However, there are some attacks for which there is no known prevention methods. For these cases, it is necessary to use some mechanism of intrusion detection. Besides preventing the intruder to cause damages to the network, the intrusion detection system (IDS) can acquire information related to the attack techniques, helping in the development of prevention systems. In this work we propose a distributed IDS that ts the demands and restrictions of WSNs. Simulation results reveal that the proposed IDS is ecient and accurate in detecting dierent kinds of simulated attacks.